2020
DOI: 10.1016/j.wneu.2020.05.108
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Neurosurgery During the Coronavirus Disease 2019 (COVID-19) Pandemic

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 23 publications
0
47
0
1
Order By: Relevance
“…Many health care workers were transitioned to other roles, not necessarily within their scope or subspecialty of training in order to accommodate the massive influx of critically ill patients. 2 The difficulty in securing basic resources, even of cleaning supplies and basic protective equipment, due to supply chain constraints and ballooning demand meant the natural push for hospitals to heavily restrict nonemergency care.…”
Section: Difficulties In Prioritizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many health care workers were transitioned to other roles, not necessarily within their scope or subspecialty of training in order to accommodate the massive influx of critically ill patients. 2 The difficulty in securing basic resources, even of cleaning supplies and basic protective equipment, due to supply chain constraints and ballooning demand meant the natural push for hospitals to heavily restrict nonemergency care.…”
Section: Difficulties In Prioritizationmentioning
confidence: 99%
“…N eurosurgical practices around the world have been affected by the COVID-19 pandemic, initially from canceling nonemergency surgical procedures to triaging and prioritizing surgical cases as health systems recover. 1,2 The response to COVID-19 was essential to attempt to efficiently allocate resources to critically ill patients and limit spread of the disease. The side effects of this process have been that neurosurgeons must take on new risks and ethical challenges and patients face unique challenges with new limitations to health care access.…”
mentioning
confidence: 99%
“…Some authors who have reported the execution of similar changes point out that these transformations have implied real challenges, since they have needed to be rapidly trained in critical care to be able to establish and provide quality support treatment. 3 Relocation of neurosurgery personnel, priority in the implementation of treatment, decision-making within the matter of ethics, risk of generating moral damage, medicolegal risks, financial difficulties, complications in carrying out the training within short periods, barriers to complete research work, and limits to carry out selective surgeries are some of the drawbacks of this major challenge. 3 …”
mentioning
confidence: 99%
“… 3 Relocation of neurosurgery personnel, priority in the implementation of treatment, decision-making within the matter of ethics, risk of generating moral damage, medicolegal risks, financial difficulties, complications in carrying out the training within short periods, barriers to complete research work, and limits to carry out selective surgeries are some of the drawbacks of this major challenge. 3 …”
mentioning
confidence: 99%
“…In the case of physically challenged patients, social distancing of about 2 m and exposure time of less than 10 min cannot be adequately maintained. 3 …”
mentioning
confidence: 99%